A portable exotendon assisting hip and knee joints reduces muscular burden during walking. Issue 11 (3rd November 2021) - Cheng, Longfei; Xiong, Caihua; Chen, Wenbin; Liang, Jiejunyi; Huang, Bo; Xu, Xiaowei
Abstract : Assistive devices are used to reduce human effort during locomotion with increasing success. More assistance strategies are worth exploring, so we aimed to design a lightweight biarticular device with well-chosen parameters to reduce muscle effort. Based on the experience of previous success, we designed an exotendon to assist in swing leg deceleration. Then we conducted experiments to test the performance of the exotendon with different spring stiffness during walking. With the assistance of the exotendon, peak activation of semitendinosus decreased, with the largest reduction of 12.3% achieved with the highest spring stiffness ( p = 0.004). The peak activations of other measured muscles were not significantly different ( p = 0.15–0.92). The biological hip extension and knee flexion moments likewise significantly decreased with the spring stiffness ( p < 0.01). The joint angle was altered during the assisted phases with decreased hip flexion and knee extension. Meanwhile, the step frequency and the step length were also altered, while the step width remained unaffected. Gait variability changed only in the frontal plane, exhibiting lower step width variability. We conclude that passive devices assisting hip extension and knee flexion can significantly reduce the burden on the hamstring muscles, while the kinematics is easily altered.